THE IMPLEMENTATION OF E-JAS SCIENCE EDUTAINMENT TO IMPROVE ELEMENTARY SCHOOL STUDENT’S CONCEPTUAL UNDERSTANDING - Ardianti, Sekar Dwi; Wanabuliandari, Savitri; Rahardjo, Susilo (Department of Integrated Science, Faculty of Mathematics and Natural Sciences, Universitas Negeri Semarang in Collaboration with Perkumpulan Pendidikan IPA Indonesia, 2019)
This research aims to unveil the improvement of elementary school student’s conceptual understanding through the implementation of E-Jas Science Edutainment. This research is a pre-experimental research with the design of one group pretest and posttest. The sample of the research uses purposive sampling technique. The result of the Normalized-Gain research shows that there is an improvement of student’s achievement under the criteria of medium (28.57%) and high (71.43 %). The classical result shows the normalized gain of 71% or 0.71, which means that student’s improvement was really high. The result shows that the implementation of E-JAS Science Edutainment can improve student’s learning achievement.